2018
DOI: 10.1002/jcb.28201
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of dysregulated lncRNA‐associated ceRNA network in colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the most frequently diagnosed digestive system cancer. The aim of the present study was to investigate the interactions among messenger RNAs (mRNAs), microRNAs (miRNAs), and long noncoding RNAs (lncRNAs) in CRC to reveal the mechanisms of CRC. Differentially expressed genes (DEGs) were identified from public gene expression data sets.One thousand eighty-one common dysregulated mRNAs in two data sets were identified. Gene function analysis and protein-protein interaction networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 62 publications
(103 reference statements)
2
28
0
Order By: Relevance
“…Previously, LINC00365 expression was reported as 3.12 ± 1.99 in CRC tissues, which was significantly higher than that in the adjacent normal intestinal mucosa (0.98 ± 0.50). 24 In this study, nearly 90% (20/22) of CRC tissues displayed a significant elevation in LINC00365 expression levels ( Figure 1A). LINC00365 expression was also markedly elevated in tumor tissues with lymph node metastasis, vascular invasion, and nerve invasion ( Figure 1B-D).…”
Section: Linc00365 Is Upregulated In Crc Tissues and Cell Linesmentioning
confidence: 50%
“…Previously, LINC00365 expression was reported as 3.12 ± 1.99 in CRC tissues, which was significantly higher than that in the adjacent normal intestinal mucosa (0.98 ± 0.50). 24 In this study, nearly 90% (20/22) of CRC tissues displayed a significant elevation in LINC00365 expression levels ( Figure 1A). LINC00365 expression was also markedly elevated in tumor tissues with lymph node metastasis, vascular invasion, and nerve invasion ( Figure 1B-D).…”
Section: Linc00365 Is Upregulated In Crc Tissues and Cell Linesmentioning
confidence: 50%
“…Hub genes have been shown to be functionally signi cant and highly interconnected with nodes in a module. In order to screen the top ranked genes with critical role in the protein-protein network (PPI), we construct PPI by uploading all genes in the selected module to the Search Tool for the Retrieval of Interacting Gene (STRING) database (http://www.string-db.org/) [17]. The Cytoscape software was further applied to perform the network analysis and the genes with top 10 degree were identi ed as hub genes [18].…”
Section: Hub Gene Analysis and Validationmentioning
confidence: 99%
“…lncRNA-miRNA-mRNA ceRNA network was constructed by "GDCRNATools" (http://bioconductor.org/packages/devel/ bioc/html/GDCRNATools.html) package in R software based on starbase database [13]. The nodes and edges were virtualized by Cytoscape 3.7.2.…”
Section: Lncrna-mirna-mrna Cerna Network Constructionmentioning
confidence: 99%
“…Dysregulation of lncRNA HOTAIR, H19, MALAT1, SNHG7, GAS8-AS, and NEAT1 were extensively well-studied and have been demonstrated to contribute in tumorigenesis and poor prognosis [5,[8][9][10][11][12]. A mounting of investigations have shown that lncRNAs exert their function through competing for endogenous RNA (ceRNA) crosstalk [13]. For instance, it has been shown that lncRNA SCARNA2 was overexpressed in COAD tissues and it remarkably correlated to chemoresistance via targeting miR-342-3p to upregulate EGFR and BCL2 in COAD cells [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation